Legal Aspects of Land Ownership in Batam's Old Villages: A Notarial Perspective - M. Tartib; Henry Aspan; Darwis Anatami; Etty Sri Wahyuni (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study examines the complex interplay between formal legal structures, customary practices, and rapid urban development in shaping land ownership dynamics in Batam's old villages (kampung tua). Through a qualitative case study approach, incorporating document analysis, semi-structured interviews, and field observations, we investigate the challenges in reconciling traditional land rights with modern property laws in the context of Batam's development as a free trade zone. Our findings reveal that approximately 70% of land parcels in the studied villages lack formal titles, highlighting the prevalence of informal ownership systems. The research identifies significant legal pluralism, where national land laws, local regulations, and customary (adat) practices coexist and often conflict. Notaries emerge as key actors navigating this complex landscape, often expanding beyond their formal mandate to mediate between different systems of authority and ownership. The study underscores the limitations of current legal frameworks in addressing the unique challenges of land administration in rapidly urbanizing areas with strong customary traditions. We propose the need for more adaptive land governance approaches that can accommodate both formal and informal ownership structures, including specialized legal frameworks for recognizing customary land rights in urban contexts. This research contributes to the broader understanding of land rights issues in the face of rapid urban development and offers insights for policymakers, legal practitioners, and urban planners grappling with similar challenges in other developing regions.